1997
DOI: 10.1007/bf02614373
|View full text |Cite
|
Sign up to set email alerts
|

A branch-and-cut algorithm for the equicut problem

Abstract: We describe an algorithm for solving the equicut problem on complete graphs. The core of the algorithm is a cutting-plane procedure that exploits a subset of the linear inequalities defining the convex hull of the incidence vectors of the edge sets that define an equicut. The cuts are generated by several separation procedures that will be described in the paper. Whenever the cutting-plane procedure does not terminate with an optimal solution the algorithm uses a branch-and-cut strategy. We also describe the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 12 publications
0
56
0
Order By: Relevance
“…In most works on exact graph partitioning (see e.g. [2,18]), sets like Random and RandW are used for the experiments. We added the sets of random regular and random planar graphs here, because we believe that more structured graph classes should also be considered with respect to their bigger relevance for practical applications.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most works on exact graph partitioning (see e.g. [2,18]), sets like Random and RandW are used for the experiments. We added the sets of random regular and random planar graphs here, because we believe that more structured graph classes should also be considered with respect to their bigger relevance for practical applications.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This modified length function does not change the analysis but it is reported that the algorithm behaves better 2 We write Ç £ to denote the "smooth" O-calculus hiding logarithmic factors. 3 A full version of this paper including all proofs can be found in [30].…”
Section: Implementation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes methods dedicated to the bipartitioning case [32,93,64,153,11,12,50,52,63] and some methods that solve the general graph partitioning problem [65,154]. Most of the methods rely on the branch-and-bound framework [106].…”
Section: Exact Methodsmentioning
confidence: 99%
“…Alternatively, this latter constraint added to the max-cut problem gives the equicut problem which can be motivated by an application to Coulomb glasses in theoretical physics. Motivated by this application, Anjos et al [5] recently proposed an enhanced branch-and-cut algorithm for equicut based on an approach proposed by Brunetta et al [13].…”
Section: Introductionmentioning
confidence: 99%